1991
DOI: 10.3354/dao010001
|View full text |Cite
|
Sign up to set email alerts
|

Blood chemistry of bacterial gill disease in brook trout Salvelinus fontinalis

Abstract: Blood chemistry was examined in brook trout Salvelinus fontinalis suffering from bacterial gdl disease (BGD) and compared to normal healthy fish under identical conditions. Infected fish showed a marked decrease in serum Na+, Cl-and in osmolality, and a concommitant haemoconcentration as indicated by the increased serum protein and increased packed cell volume. Fish with BGD exhibited an mcreased rate of respiration (tachybranchia) but were not hypoxemic, suggesting that compensatory mechanisms, such as tachyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…Blood PaO 2 is the primary stimulus for respiration in trout, although elevated PaCO 2 , and/or acidemia, may also contribute towards stimulating respiration (Perry and Wood 1989). Thus, the most economical explanation for the commonly observed phenomenon of tachybranchia in BGDinfected fish, namely the existence of an hypoxemia (Wakabayashi and Iwado 1985a,b;Ferguson 1989;Byrne et al 1991;Speare et al 1991a), is further corroborated by these findings.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Blood PaO 2 is the primary stimulus for respiration in trout, although elevated PaCO 2 , and/or acidemia, may also contribute towards stimulating respiration (Perry and Wood 1989). Thus, the most economical explanation for the commonly observed phenomenon of tachybranchia in BGDinfected fish, namely the existence of an hypoxemia (Wakabayashi and Iwado 1985a,b;Ferguson 1989;Byrne et al 1991;Speare et al 1991a), is further corroborated by these findings.…”
Section: Discussionsupporting
confidence: 64%
“…Byrne et al (1991) suggested that the drop in serum [Na + ] and [C1-] was the dominant event in the pathogenesis of subacute/chronic BGD. Findings in the present study can neither corroborate nor refute this claim, but the dramatic drop in PaO 2 suggests that hypoxemia may also be a major mechanism, at least during the acute stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Many parasitic infections, as well as chemical irritation, will result in gill mucus production that inhibits carbon dioxide excretion and causes respiratory acidosis (Powell & Perry 1996, Powell et al 1998, 2000. Byrne et al (1991) demonstrated that brook trout Salvelinus fontinalis challenged with Flavobacterium branchiophilum showed no significant change in blood pH 1 and 4 d postchallenge. In contrast, rainbow trout (Byrne et al 1995) showed a significant decrease in blood pH 24 h postchallenge.…”
Section: Discussionmentioning
confidence: 99%
“…These include artificial lighting, loud or aversive sound, arousing odours, unsuitable temperatures or substrates, restricted movement, reduced retreat space, forced proximity to humans, reduced feeding opportunities, manipulation of fish groups, transportation (e.g. Barreto and Volpato 2006;Morgan and Tromborg 2007), handling (Brydges et al 2009), air exposure (White et al 2008), the presence of predators (Barreto et al 2003), presence of chemicals (Neely 1979;Israeli-Weinstein and Kimmel 1998;Pane et al 2004;Scott and Sloman 2004), diseases (Byrne et al 1991), nanotubes ), cyanobacteria (Ernst et al 2007) and poor water quality in general (ammonia (NH 4 )/nitrate (NO 3 ) excess, etc. ).…”
Section: Ventilatory Activitymentioning
confidence: 99%